Bijective Proofs of Partition Identities of MacMahon, Andrews, and Subbarao - Shishuo Fu; James Sellers (Discrete Mathematics & Theoretical Computer Science, 2014)
We revisit a classic partition theorem due to MacMahon that relates partitions with all parts repeated at least once and partitions with parts congruent to $2,3,4,6 \pmod{6}$, together with a generalization by Andrews and two others by Subbarao. Then we develop a unified bijective proof for all four theorems involved, and obtain a natural further generalization as a result.